ANALISIS DAMPAK PENERAPAN KURIKULUM MERDEKA TERHADAP MINAT BELAJAR SISWA DI KELAS IVANALYSIS OF THE IMPACT OF THE IMPLEMENTATION OF THE MERDEKA CURRICULUM ON STUDENTS’ LEARNING INTEREST IN GRADE IV - Nurhudayah Manjani; Siregar, Hanif Luthfi; Aprilia, Nada; Lubis, Putri Ramadhani; Purba, Dearni Asri Br; Sari, Nopyta; Lubis, Laila Hidayati (Jurnal Merah Putih Sekolah Dasar, 2024)
The crucial aspect in developing high-quality human resources is education. The Indonesian government has developed and implemented various policies and curricula, including the Merdeka Curriculum. The goal of the Merdeka Curriculum is to provide more freedom and autonomy to schools, teachers, and students during the learning process, with the hope of increasing students' interest and motivation to learn. The objective of this study is to investigate how the Merdeka Curriculum affects the quality of education in Indonesia. This study collected data from 50 fourth-grade students through a quantitative survey method. The results showed that students became more active in learning activities, took responsibility for their tasks, and were more enthusiastic in learning activities. It is hoped that these findings will contribute to the development of education policies and serve as a reference for teachers in optimizing the implementation of the Merdeka Curriculum.